2018
DOI: 10.1590/0034-7167-2017-0248
|View full text |Cite
|
Sign up to set email alerts
|

Self-care of elderly people after the diagnosis of acquired immunodeficiency syndrome

Abstract: Data show the elderly people's lack of knowledge about HIV/AIDS transmission, the experience of being elderly and having HIV/AIDS, caring for oneself and life after diagnosis of HIV/AIDS in their daily lives. Final considerations: The diagnosis of HIV/AIDS seropositivity in the elderly generates a blend of feelings and fears that lead to food changes, adherence to treatment and the renunciation of daily and social habits, manifested as ways of self-care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
4
0
5
Order By: Relevance
“…This status predisposes to faster disease progression, lower therapeutic success, and higher mortality after diagnosis, according to certain authors. (20,21) The factors that determine CD4+ T cell response are partially elucidated; however, advanced age, longstanding disease and low baseline cell counts are risk factors for incomplete immune recovery. (22) It is worth noting that, at month 6, there was an average increase of 139.63 cells.…”
Section: ❚ Resultsmentioning
confidence: 99%
“…This status predisposes to faster disease progression, lower therapeutic success, and higher mortality after diagnosis, according to certain authors. (20,21) The factors that determine CD4+ T cell response are partially elucidated; however, advanced age, longstanding disease and low baseline cell counts are risk factors for incomplete immune recovery. (22) It is worth noting that, at month 6, there was an average increase of 139.63 cells.…”
Section: ❚ Resultsmentioning
confidence: 99%
“…A study conducted with elderly patients with HIV showed that a very low number of HIV rapid tests were performed in the elderly. 19 In Minas Gerais State, Brazil, only 26.6% of 216 elderly people were tested for HIV infection. 20 Furthermore, in São Paulo State, ALENCAR and CIOSAK interviewed some primary care physicians and nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Também identificouse um aumento considerável no número da procura ao serviço do CTA pelos idosos no ano de 2007, o que foi justificado pelo empenho do MS nas campanhas de prevenção voltadas a esse grupo 25 . Tal constatação mostra a importância em se reconhecer o perfil dos usuários do serviço do CTA, a fim de direcionar políticas públicas ao público alvo identificado 23,26 .…”
Section: Perfil Dos Usuários Nos Anos 2000unclassified
“…O motivo mais frequente quanto à procura do serviço é o risco da exposição a alguma IST, justificado pelo não uso do preservativo pela maioria dos usuários, o tipo de parceria sexual foi de relacionamentos homossexuais e o tipo de IST mais prevalente foram as hepatites B e C 28 . Pelo fato de um dos objetivos iniciais do CTA ser o combate e prevenção ao HIV/AIDS, existem mais estudos que relatam as características epidemiológicas e comportamentais dos usuários com a presença do vírus do HIV no organismo que o perfil dos usuários de forma geral [26][27][28] .…”
Section: Perfil Dos Usuários Nos Anos 2000unclassified
See 1 more Smart Citation